The Potential of Natural Levodopa in Koro Benguk Seeds (Mucuna pruriens) for Treatment in Parkinson's Disease - Aisya Nur Abida; Maida sania salsabila; Maharani, Nyoman Ayu Anindya; Belynda Rahmalia Sanceska Wahyudi; Aisya Yafis Iqlima; Devi Chandra Kirana; Andina Nabilah Mario; Herpan Syafii Harahap (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Mucuna pruriens also known as velvet bean (koro benguk) is a plant commonly found in tropical regions, including Indonesia. Mucuna pruriens is known to contain high levels of Levodopa, making it a potential natural treatment for Parkinson's disease. Parkinson's disease is a neurodegenerative disorder characterized by tremors, rigidity, bradykinesia, and postural instability. The estimated global incidence of Parkinson's disease in 2024 is expected to reach 12 to 17 million patients. Synthetic Levodopa has been the standard and proven effective therapy for Parkinson's disease. The method used in the preparation of this article is a literature review by collecting relevant and focused articles. The literature sources were accessed through comprehensive searches in three databases (Pubmed, Google Scholar, and Researchgate) from 2014 to 2024, using keywords such as “Mucuna pruriens,” “Levodopa,” and “Parkinson's disease.” The result of the literature review indicates that Levodopa is the dominant active component found in Mucuna pruriens compared to other compounds. The naturally occurring Levodopa functions as a precursor to dopamine, which plays a role in the treatment of Parkinson's disease, thus it can be developed into a complementary therapy in regions with abundant resources.